2011
DOI: 10.1007/s10482-011-9642-6
|View full text |Cite
|
Sign up to set email alerts
|

Description of a French natural wheat sourdough over 10 consecutive days focussing on the lactobacilli present in the microbiota

Abstract: Sourdoughs are complex ecosystems which are widely used to produce baked goods. This study aimed to provide a dynamic description of an industrial French sourdough ecosystem over 10 consecutive days. The sourdough was obtained from a natural fermentation that has been propagated over several years by the traditional backslopping method. The physico-chemical properties (pH, temperature, total titratable acidity) and the diversity of the lactobacilli among the microbiota were analyzed. A culture-dependent approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 26 publications
2
9
1
1
Order By: Relevance
“…In previous studies of French sourdoughs, L. sanfranciscensis was either not found (Valcheva et al, 2006;Vera et al, 2011) or detected but not predominantly (Ferchichi et al, 2007;Robert et al, 2009;Valcheva et al, 2005). Yet, with the exception of reports by Groenewald et al (2006), L. sanfranciscensis has only been isolated from sourdough and is known to be dominant (Lattanzi et al, 2013;Minervini et al, 2012a;Scheirlinck et al, 2008).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In previous studies of French sourdoughs, L. sanfranciscensis was either not found (Valcheva et al, 2006;Vera et al, 2011) or detected but not predominantly (Ferchichi et al, 2007;Robert et al, 2009;Valcheva et al, 2005). Yet, with the exception of reports by Groenewald et al (2006), L. sanfranciscensis has only been isolated from sourdough and is known to be dominant (Lattanzi et al, 2013;Minervini et al, 2012a;Scheirlinck et al, 2008).…”
Section: Discussionmentioning
confidence: 85%
“…In fact, previous works on French sourdoughs have considered only LAB diversity (Ferchichi et al, 2007;Robert et al, 2009;Valcheva et al, 2005;Vera et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ten grams of sourdough was homogenized with 90 ml of sterile peptone water (0.1% [wt/vol] peptone and 0.9% [wt/vol] NaCl) solution (24,47). Lactic acid bacteria were counted using sourdough bacteria (SDB) agar medium, supplemented with cycloheximide (0.1 g liter Ϫ1 ).…”
Section: Sourdoughsmentioning
confidence: 99%
“…Characterizations of Turkish (Gület al, 2005), Thai (Luangsakulet al, 2009), Chinese (Zhang et al, 2011) and French (Vera et al, 2012) sourdoughs have also been reported. However, research published in Brazil about sourdoughs is still scarce, even though the bread is widely consumed.…”
Section: Introductionmentioning
confidence: 98%
“…Yeasts are generally counted in lower levels (7 log CFU/g) and can even be absent. The major part of the yeasts belong to the genera Saccharomyces and Candida (Vera et al, 2012).…”
Section: Introductionmentioning
confidence: 99%